Translation in Students Language Performance of English Language Course in Udayana University - Darmasetiyawan, I Made Sena (Lingual Journal of Language and Culture; Vol 2 No 2 (2016)DO - 10.24843/LJLC.2016.v02.i02.p07, 2016)
To the second language learner, translation has serves an important role as the initial point to their language comprehension. Language levels and unit cannot be separated from the comprehension towards language meaning. Therefore, during classroom activities; when the students were asked to provide swift language expression to their opinion or answer, they will focus on generating equivalencies of both languages. This translation method can be seen from the generation of lexical level, comprehending meaning, and forming text.
Keywords: language comprehension, classroom activities, equivalencies